Nano-Polyoxotungstate [Cu20P8W48] Immobilized on Magnetic Nanoparticles as an Excellent Heterogeneous Catalyst Nanoreactors for Green Reduction of Nitrophenol Compounds - Reza Haddad; Ali Roostaie (Journal of Spectroscopy)
In this study, Cu20-polyoxotungstate [Cu20Cl(OH)24(H2O)12(P8W48O184)]25− supported on a magnetic substrate was used as a high-performance green method for the reduction of nitrophenol compounds such as 4-nitrophenol (4-NP) and 2,4,6-trinitrophenol (2,4,6-TNP). [Fe3O4@SiO2-NH2-Cu20P8W48] as heterogeneous magnetic nanocatalyst was synthesized and characterized by FT-IR, SEM, TEM, VSM, and TGA. This nanocatalyst has an excellent efficiency in the reduction of nitrophenol compounds to aminophenol compounds. The UV-Vis absorption spectrum is used at different times to evaluate the progress of the reaction. Under optimal conditions, 100% conversion and selectivity in reduction of 4-NP and 2,4,6-TNP to 4-AP and 2,4,6-TAP were obtained, respectively. In addition, after the reaction, the [Fe3O4@SiO2-NH2-Cu20P8W48] was recovered using an external magnetic field and used for the next cycle. The results showed that the nanocatalyst can perform eight consecutive cycles without any significant decrease in efficiency. In the end, according to the results, the proposed mechanism for this reaction was reported.